NEW FACE OF RELIGIOUS AFFAIR MINISTER AND THE EPISTEMOLOGY OF QUR’ANIC ETHICS: A SYNCHRONIC-DIACHRONIC READING ON QS. AL-HUJURĀT (49): 11-13 - Egi Tanadi Taufik (Islam Futura, 2021)
Aesthetic phenomenon that is happening in Indonesia is suspected by the election year. Debates between presidents that contain "contempt of contempt", either by quoting the mistakes of a presidential candidate in the past or by searching for incumbents presidential incumbents positively, raises concern for the writer. The immoral act was followed by the phenomenon of the appointment of a former military officer as the Minister of Religion of the Republic of Indonesia in the cabinet “Indonesia Maju” for 2019-2024 working period. Through the reflection on these backgrounds, the author initiated to reconstruct Islamic ethics in the present context. This paper uses the interpretation of Ibn Jarir al-Tabari (d. 923) in his Jamī 'al-Bayan, Jalal al-Din al-Suyuthi (d. 1505) in his Durr al-Mantsur, and Hamka (d. 1981) in his Tafsir Al-Azhar. The author also reads the development of ethical concepts in various literatures diachronically, for example the concept of ethics in al-Miskawaih's perspective and the social-humanity ethics of Austin Fagothey. The final results in this paper are expected to provide a new horizon for various the rightaway polemics. The epistemology of the Qur'ani ethic formed by these three cross-period commentators shows a conclusion that the ethical values in Kalam Allah need to be formatted in humanitarian missions. The author claims HAMKA's Al-Azhar Tafsir as an interpretation of social ethics in the Qur'an that is most relevant to the current context in Indonesia. HAMKA sees that the Qur'anic ethics is able to bring the concepts of faith and piety into social awareness to fight poverty, crime, discrimination, intolerance, and disagreements. The concept embodies the integration between Qur’an axiology in QS. al-Hujurat (49): 11-13 with universal humanist principles such as equality, justice, democracy, protection of rights, and peace. All of these values can be diplocrammed with the spirit of the election of the Indonesian republic's minister of religion who understands nationalism and spiritualism.